Optimal statistical decisions - DeGroot, Morris H. (New York : McGraw-Hill, 1970)
This book provides a thorough discussion in the theory and methodology of optimal statistical decisions. The volume represents a landmark. It still remains the clearest introduction to Bayesian statistical decision theory even in, this, a paperback reprint of the original book dating back to 1970 .
Includes index.
Includes bibliographical references: p. 447-471.
aia 14/05/2018
Loans
Keywords: Game theory; Statistical decision